Teacher voice care: analysis of an action offered in a semi-face mode (Research, Society and Development, 2023)
Objective: to analyze the knowledge about self-care practices with the voice acquired by teachers comparing two periods. Method: A cross-sectional study was conducted with 129 teachers who attended a blended course and answered a questionnaire to assess the knowledge acquired. Participants were divided into two groups: G1 (n=74) and G2 (n=55), including those who responded six months and one year after completing the course, respectively. The collected data were subjected to statistical tests. Results: When comparing the two groups, a difference (p=0.031) was found in the category “voice self-care practices included in daily professional life”, in which G1 was higher (100.0%) than G2 (92,7%). There was also a difference (p=0.004) associated with the responses to “think about using strategies to improve the work environment” (G1=75.7%; and G2=94.5%). Conclusion: The most reported aspects were “concern with hydration,” “performing vocal exercises” and “not forcing the voice/not screaming”. A little difference was found between the groups.